2023
DOI: 10.3390/ijms24098167
|View full text |Cite
|
Sign up to set email alerts
|

A Tumor and Immune-Related Micro-RNA Signature Predicts Relapse-Free Survival of Melanoma Patients Treated with Ipilimumab

Abstract: Despite the unprecedented advances in the treatment of melanoma with immunotherapy, there continues to be a major need for biomarkers of clinical benefits and immune resistance associated with immune checkpoint inhibitors; microRNA could play a vital role in these efforts. This study planned to identify differentially expressed miRNA molecules that may have prognostic value for clinical benefits. Patients with surgically operable regionally advanced melanoma were treated with neoadjuvant ipilimumab (10 mg/kg i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…With regard to gene expression profiling, a recent study reported a 4-miRNA signature, the baseline expression levels of which were significantly associated with the therapeutic benefits of neoadjuvant ipilimumab. 105 Biomarkers that have been explored in clinical trials of neoadjuvant therapy are summarized in Table 3 per each treatment strategy.…”
Section: Personalized Medicine In Adjuvant and Neoadjuvant Therapy Fo...mentioning
confidence: 99%
“…With regard to gene expression profiling, a recent study reported a 4-miRNA signature, the baseline expression levels of which were significantly associated with the therapeutic benefits of neoadjuvant ipilimumab. 105 Biomarkers that have been explored in clinical trials of neoadjuvant therapy are summarized in Table 3 per each treatment strategy.…”
Section: Personalized Medicine In Adjuvant and Neoadjuvant Therapy Fo...mentioning
confidence: 99%
“…Other biotechnological companies, like OPKO Health, Inc., Miami, FL, USA, Alnylam Pharmaceuticals, Cambridge, MA, USA, Interna Technologies, Utrecht, The Netherlands and Mello Biotech, Santa Fe Springs, CA, USA are in the screening phase [235]. Additionally, Rosetta Genomics, Princeton, NJ, USA [239], RXi Pharmaceuticals, Marlborough, MA, USA [240], Phio Pharmaceuticals, Marlborough, MA, USA [241], Asuragen, Inc., Austin, TX, USA [242], Sirnaomics, Inc., Germantown, TN, USA [243], Bristol-Myers Squibb, New York, NY, USA [244], and Dicerna Pharmaceuticals, Lexington, KY, USA [245] have developed miRNA-based biomarkers. A snapshot of the progress in the biopharmaceutical pipeline that could increase the number of miRNA therapeutics is shown in Table 2.…”
Section: Mirna-based Therapies In Clinical Practicementioning
confidence: 99%
“…As against the physiological state of normal tissues, the expression profile of miRNA in cancer cells shows abnormal changes. Based on the effect of miRNA on its target genes, it has been confirmed that miRNA can inhibit or promote tumour growth [ 8 ]. The increase of oncogenic miRNA is caused by the abnormal amplification and ectopic of miRNA genes.…”
Section: Introductionmentioning
confidence: 99%